Implementasi Sistem Bagi Hasil Kebun Kelapa Perspektif Hukum Ekonomi Islam (Studi Kasus di Kebun Bapak Karimun Desa Kuala Lagan Kecamatan Kuala Jambi) - Dewa Saputra; M. Arif Musthofa; Zeni Sunarti; Kurniawan Kurniawan; Triyana Wulandari; Hasna Dewi (Journal of Innovative and Creativity, 2025)
The purpose of this study was to determine the implementation of the profit-sharing system in Mr. Karimun's coconut plantation in Kuala Lagan Village, Kuala Jambi District, and to analyze the profit-sharing system from an Islamic economic perspective. This study employed a qualitative approach with descriptive methods. The data collected in this study were primary and secondary sources. The techniques used by the researcher to obtain objective and valid data or information were observation, interviews, and documentation. The data analysis process consisted of three main components: data reduction, data presentation, and verification (conclusions). The conclusion obtained is that the profit-sharing system is carried out with a general profit-sharing pattern of 50:50 or according to contribution, the coconut plantation profit-sharing system is implemented verbally based on mutual trust at Mr. Karimun's Garden in Kuala Lagan Village, Kuala Jambi Regency. Although this collaboration boosts the economy and strengthens social ties, it is still administratively ineffective because there is no formal or written agreement and costs and results are not recorded transparently. From the perspective of Islamic economic law, the profit-sharing system of coconut plantations at Mr. Karimun's Garden in Kuala Lagan Village is basically permissible (mubah) as long as it involves mutual agreement (taradhi) and avoids fraud or injustice. However, because several things are not in line with Islamic values ​​of the protection of rights, justice, and clarity in the agreement, such as the absence of written records that outline rights and responsibilities and a more logical way to distribute resources, this practice needs to be improved and strengthened to be more in line with Sharia teachings, which emphasize justice, legal clarity, and the protection of all individuals involved